Mechanically switchable micro-patterned adhesive for soft material applications - Johannes, Karl; Calahan, Kristin; Bowen, Leah; Zuetell, Emily; Long, Rong; Rentschler, Mark (Extreme Mechanics Letters, 2022)
Many switchable adhesives controlled by an external stimulus have been developed for interaction with effectively rigid materials, e.g., in silicon wafer processing and wall climbing robots. However, applications such as medical devices and automated food handling demand switchable adhesives for soft materials. In this work, we apply equibiaxial tensile strain to an elastomeric micro-patterned surface to modulate its adhesion with both rigid and soft materials. First, we measure the geometric changes of frustum-shaped features on the micro-patterned surface under varying applied equibiaxial strains. We then experimentally characterize adhesion of the equibiaxially strained micro-patterned surface in contact with rigid and soft spherical probes. Experimental results show that the applied strain on the micro-patterned surface can substantially influence its adhesion behavior with both the rigid and soft probes. However, the underlying mechanism is different. For the rigid probe, the dominating mechanism is that the applied strain reduces the system compliance by decreasing the backing layer thickness of the micro-patterned surface. For the soft probe, the primary role of the applied strain is to influence the true contact area by changing the shape and spacing of the frustum-shaped features. Finally, we demonstrate the elastomeric micro-patterned surface as a switchable adhesive gripper for both soft and rigid objects.